Revolution deferred : the painful birth of post-apartheid South Africa / Martin J. Murray. - Murray, Martin J. (Verso, 1994)
This volume explores the social forces that are currently shaping the new South Africa and provides detail on the political and ideological rifts in the liberation movement, including analysis of the "homelands" parties, the trade unions and the ANC.